Uso de la resonancia magnética nuclear para la determinación de curcuminoides en cúrcuma y curry producidos y vendidos en Costa Rica - Solano Arias, Godofredo (2014)
Turmeric (Curcuma longa) rizhome is used as a spice to give colour to food, but its extracts have also shown many interesting biological activities that make C. longa valuable for cultivation and consumption. The active compounds in turmeric are known as curcuminoids and their content in the rhizome varies by many factors. It is therefore important to have analytical methods to monitor the quality of the rhizome and the derived products such as curry. Here we show a simple method using 1H-‐‐NMR as a tool for the quantification of curcuminoids in crude extracts. The preliminary results showed that the content of curcuminoids in CostaRican rhizome crops is similar to that from other regions of the world. A survey of the curcuminoids in turmeric and curry sold in local convenience stores shows that the curcumin content of turmeric is in the range shown in other studies, but that curry is close to the lower values reported in those studies.